2022
DOI: 10.1111/bph.15949
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing nitazoxanide as a novel anti‐atherosclerotic drug based on mitochondrial uncoupling mechanisms

Abstract: Background and Purpose The anthelmintic drug nitazoxanide has a mitochondrial uncoupling effect. Mitochondrial uncouplers have been proven to inhibit smooth muscle cell proliferation and migration, inhibit NLRP3 inflammasome activation of macrophages and improve dyslipidaemia. Therefore, we aimed to demonstrate that nitazoxanide would protect against atherosclerosis. Experimental Approach The mitochondrial oxygen consumption of cells was measured by using the high‐resolution respirometry system, Oxygraph‐2K. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Previous studies reported that nitazoxanide and tizoxanide could stimulate autophagy responses (Fan et al, 2019; Lam et al, 2012; Shou et al, 2020). Our previous works found that nitazoxanide and tizoxanide induced autophagy in A10 cells, RAW264.7 macrophages and HepG2 cells (F.Li, Jiang, et al, 2022 ; Ma et al, 2023). Here, we found that both nitazoxanide and tizoxanide treatment increased LC3 II and LC3 II/LC3 I ratio in MRC‐5 cells (Figure S2a–d).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies reported that nitazoxanide and tizoxanide could stimulate autophagy responses (Fan et al, 2019; Lam et al, 2012; Shou et al, 2020). Our previous works found that nitazoxanide and tizoxanide induced autophagy in A10 cells, RAW264.7 macrophages and HepG2 cells (F.Li, Jiang, et al, 2022 ; Ma et al, 2023). Here, we found that both nitazoxanide and tizoxanide treatment increased LC3 II and LC3 II/LC3 I ratio in MRC‐5 cells (Figure S2a–d).…”
Section: Resultsmentioning
confidence: 98%
“…Our previous studies had shown that nitazoxanide and its active metabolite tizoxanide induced mitochondrial uncoupling and activated AMPK in human hepatocellular carcinoma cells (HepG2 cells) and vascular smooth muscle cells (A10 cells) (F. Li, Jiang, et al, 2022; Ma et al, 2023); here, we examined the effect of nitazoxanide and tizoxanide in human embryonic lung fibroblasts (MRC‐5 cells). Reducing the membrane potential and increasing oxygen consumption were characterizations of mitochondrial uncoupling effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations